Super-resolved live-cell imaging using random illumination microscopy - Mangeat, Thomas; Labouesse, Simon; Allain, Marc; Negash, Awoke; Martin, Emmanuel; Guénolé, Aude; Poincloux, Renaud; Estibal, Claire; Bouissou, Anaïs; Cantaloube, Sylvain; Vega, Elodie; Li, Tong; et al. (Cell reports methods, 2021)
Current super-resolution microscopy (SRM) methods suffer from an intrinsic complexity that might curtail their routine use in cell biology. We describe here random illumination microscopy (RIM) for live-cell imaging at super-resolutions matching that of 3D structured illumination microscopy, in a robust fashion. Based on speckled illumination and statistical image reconstruction, easy to implement and user-friendly, RIM is unaffected by optical aberrations on the excitation side, linear to brightness, and compatible with multicolor live-cell imaging over extended periods of time. We illustrate the potential of RIM on diverse biological applications, from the mobility of proliferating cell nuclear antigen (PCNA) in U2OS cells and kinetochore dynamics in mitotic S. pombe cells to the 3D motion of myosin minifilaments deep inside Drosophila tissues. RIM's inherent simplicity and extended biological applicability, particularly for imaging at increased depths, could help make SRM accessible to biology laboratories. [Display omitted] •RIM exploits speckled illumination for 3D super-resolution microscopy of live cells•The spatiotemporal resolution and toxicity levels of RIM match that of 3D-SIM•RIM's intrinsic robustness to aberrations allows increased depth of imaging•RIM is low cost and easy to use, making the method accessible to many researchers Super-resolution optical microscopy (SRM) has been instrumental to rapid progress in cell biology. Many SRM variants are now available with different compromises between phototoxicity, spatiotemporal resolutions, and sensitivity to aberrations. Yet, established SRM techniques, even implemented as expensive turn-key systems, require expert know-how at the instrumentation or image reconstruction levels to operate at the best of their capabilities. The present challenge is to develop a simple, easy to use, and low-cost SRM technique that would combine artifact-free super-resolution, robustness to aberration, low toxicity, and good temporal resolution for routine functional imaging of live cells within normal or pathological tissues. Mangeat et al. use speckled illumination to develop a simple, low-cost super-resolution microscopy method, called RIM, that matches traditional SIM performances in a more robust fashion. RIM's intrinsic robustness to aberrations, high spatiotemporal resolution, and low toxicity allow dynamic live-cell imaging at increased depth as a routine technique.